Analysis of Enterprise Risk Management Implementation in Managing Risk in the Financial Industry - Dona Elvia Desi; Nera Marinda Machdar; Adler Haymans Manurung (Dinasti Publisher, 2025)
The financial industry faces increasingly complex challenges in managing various types of risks that threaten the stability and sustainability of its operations. The global financial crisis of 2008 provided valuable lessons on the importance of an integrated and comprehensive risk management system. This event prompted regulators and practitioners to adopt a more holistic approach to identifying, measuring, and controlling risk.